2021
DOI: 10.3390/agriculture11070638
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Some Antioxidants as Attenuators of Heat Stress on Chicken Meat Characteristics

Abstract: The study evaluated the effect of dietary chromium and vitamin C, Zinc, and sorrel wood powder supplements on chicken health and the nutritional, textural, and sensorial quality of chicken meat. A total of 120 Cobb 500 chickens (heat stress, 32 °C) were assigned into four treatments: control diet (C) and three test diets including 200 µg/kg diet chromium picolinate and supplemented with: 0.25 g vitamin C(VC)/kg diet (E1), 0.025 g Zn/kg diet (E2), and 10 g creeping wood sorrel powder (CWS)/kg diet (E3). Crude p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The analysis of proximate composition (dry matter, crude protein, ether extract, and ash) of plant and meat samples (breast and thigh) was determined according to [ 23 ]. Dry matter (ISO 6496/2001) and ash (ISO 2171/2010) were determined by the gravimetric method, crude protein (ISO 5983-2/2009) was analyzed by the Kjeldahl method, and ether extractives were performed by extraction in organic solvents (SR ISO 6492/2001).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of proximate composition (dry matter, crude protein, ether extract, and ash) of plant and meat samples (breast and thigh) was determined according to [ 23 ]. Dry matter (ISO 6496/2001) and ash (ISO 2171/2010) were determined by the gravimetric method, crude protein (ISO 5983-2/2009) was analyzed by the Kjeldahl method, and ether extractives were performed by extraction in organic solvents (SR ISO 6492/2001).…”
Section: Methodsmentioning
confidence: 99%
“…However, the current increase in the incidence of heat waves due to climate change further heightens HS concerns ( Chauhan et al, 2021 ). Recently, interests have involved the extensive use of bioactive substances to ameliorate HS in poultry ( Saracila et al, 2021 ) due to their beneficial effects on health and production ( Abdelli et al, 2021 ). These phytogenic feed additives can be incorporated into animal feed or water as extracts ( Gadde et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our findings on liver crude fat, other authors have shown different results on deposit tissues (breast and thigh). For example, some authors showed that Cr-Zn and Cr-VC supplementation to the diet of heat stressed broiler decreased the content of crude fat in breast (Untea et al, 2021) and thigh meat (Saracila et al, 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…Creeping wood sorrel (Oxalis corniculata, CWS) contains a wide range of phytochemicals with antioxidant properties such as flavonoids, tannins, phytosterols, polyphenols, glycosides (Sharma & Kumari, 2014). Recent studies (Saracila et al, 2020;2021a;Untea et al, 2021) have shown that diet supplemented with Cr picolinate and CWS had a positive effect on meat quality from heat-stressed broilers.…”
Section: Introductionmentioning
confidence: 99%